Operation Tirúa: Hydrographic Vision - Guzmán Montesinos (Chile), Nicolás A. (The International Hydrographic Review, 2015)
On 6 October 2013, a small commercial flight with 5 people on board and flying between Mocha Island and Tirúa off the coast of Chile went missing, leaving no traces. The Armed Forces established a search party with personnel and staff from the 3 forces. Considering the possible fall of the plane into the ocean, the Navy deployed several naval and maritime resources with the purpose of finding any signs of it. A number of vessels with hydrographic capacities searched carefully for over 20 days with no positive results. Some parts of the small plane were found 7 months later on the coast on Mocha Island. The hydrographic experiences from this operation provide a number of lessons that can be used in similar operations and to optimize the use of the resources.